2022
DOI: 10.3389/fmicb.2022.993990
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the phage trends: A comprehensive review of applications in therapy and food production

Abstract: In the present scenario, the challenge of emerging antimicrobial resistance is affecting human health globally. The increasing incidences of multidrug-resistant infections have become harder to treat, causing high morbidity, and mortality, and are posing extensive financial loss. Limited discovery of new antibiotic molecules has further complicated the situation and has forced researchers to think and explore alternatives to antibiotics. This has led to the resurgence of the bacteriophages as an effective alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 149 publications
0
1
0
Order By: Relevance
“…Despite the proven effectiveness of phages against bacterial infections in vitro and animal models, the number of clinical trials for phage therapy remains limited. This is primarily attributed to concerns about phage clearance after treatment, impurities in phage preparations, poor stability of phage preparations, and a lack of detailed knowledge about phage mechanisms of action and the potential for bacterial resistance to phages (Jaglan et al, 2022). Clinical trials examining the use of phages against P. aeruginosa infections in patients with venous leg ulcers, burn wounds, and otitis have reported no adverse effects.…”
Section: Bacteriophage Therapymentioning
confidence: 99%
“…Despite the proven effectiveness of phages against bacterial infections in vitro and animal models, the number of clinical trials for phage therapy remains limited. This is primarily attributed to concerns about phage clearance after treatment, impurities in phage preparations, poor stability of phage preparations, and a lack of detailed knowledge about phage mechanisms of action and the potential for bacterial resistance to phages (Jaglan et al, 2022). Clinical trials examining the use of phages against P. aeruginosa infections in patients with venous leg ulcers, burn wounds, and otitis have reported no adverse effects.…”
Section: Bacteriophage Therapymentioning
confidence: 99%
“…Bacteriophages (phages) are perhaps among the oldest and most prevalent biological entities that can infect and replicate within bacteria. As a result, they are crucial to maintaining the balance of an environment where bacteria are present (Jaglan et al, 2022). There is now curiosity in utilizing phage as a biocontrol weapon because of the numerous alluring properties these natural antibacterial agents possess (Sillankorva et al, 2012).…”
Section: Bacteriophagesmentioning
confidence: 99%
“…However, their usage for therapeutic purposes was discontinued in the Western world after the development of antibiotics. The lack of additional therapeutic options and the ineffectiveness of traditional antibiotics in treating and managing harmful bacterial strains have recently accelerated the revival of phage therapy (Jaglan et al, 2022). In previous study, Montso et al (2021) demonstrated that lytic phages effectively reduced E. coli O177 cells under artificial rumen fermentation conditions, and could therefore be used as a biocontrol strategy in live cattle to reduce meat and milk contamination in slaughterhouses and milking parlors, respectively.…”
Section: Bacteriophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…They can serve as antibiotic alternatives or be combined with antibiotics for synergistic effects (22). Clinical approaches for phage therapy have been reported in several countries, such as the United States, Georgia, Poland, and Russia (23, 24). Scientific evidence supporting the benefits of phage therapy for humans and animals has steadily increased in recent decades (25).…”
Section: Introductionmentioning
confidence: 99%